In-vitro evaluation of antimicrobial efficiency of geranium waste nanomaterial against Escherichia coli and Candida albicans as an alternative to traditional antimicrobials - Maha M. Kamel; Abdelfattah Badr; Dalal Hussien M. Alkhalifah; Rehab Mahmoud; Esraa Khaled; Samah Husseiny; Sahar Abdel Aleem Abdel Aziz; Manar Bahaa El Din Mohamed; Wael N. Hozzein (Results in Chemistry)
Antimicrobial resistance remains a pressing global concern, perpetually challenging medical researchers. Exploring alternatives to traditional antibiotics, particularly those derived from natural sources such as medicinal plants, has garnered significant interest in combating this resistance. In this study, various materials including Mg nanoparticles (NPs), ZnO NPs, Geranium waste (GW), Mg NPs/GW nanocomposite, and ZnO NPs/GW nanocomposite were synthesized using green synthesis methods and characterized using diverse techniques. To evaluate their antimicrobial efficacy, a total of 250 fecal samples were randomly collected on a weekly basis (twice per week) from cattle of different age groups (6 to 9 months) over the study period. Escherichia coli (E. coli) and Candida albicans (C. albicans) were isolated and identified, and the antimicrobial activity of the synthesized materials was assessed against these pathogens. Minimum Inhibitory Concentrations (MICs) results demonstrated that Mg NPs/GW nanocomposite exhibited the most potent activity against E. coli, with a MIC of 7.81 ± 0.4 μg/mL, followed by Mg NPs. Similarly, Minimum Fungicidal Concentrations (MFCc) results indicated that Mg NPs/GW nanocomposite was the most effective against C. albicans, with an MFC of 31.25 ± 0.7 μg/mL. Notably, Mg NPs/GW nanocomposite showed promising results in controlling both E. coli and C. albicans, exhibiting lower MIC and MFC values, thus offering potential in overcoming microbial resistance to conventional antimicrobials.